A descriptive cross-sectional study about the perception of Mental Illness among HIV Counselors in Bushenyi District. - Musitwa , Moses; Lusalalira , Ignatious (Student’s Journal of Health Research Africa, 2022)
Background The HIV/AIDS pandemic has led to millions of deaths as well as disability and negative outcomes on HIV affected individual. One such disability is mental illness which has been found to lead to increased prevalence of anxiety, depression and substance abuse among people living with HIVAIDS as compared to the general population. Methodology A descriptive cross-sectional study was carried out to determine the perception of Mental Illness among HIV Counselors in Bushenyi District. A total of 30 respondents participated in the study and they were selected by use of purposive sampling procedure. Data was collected using questionnaires and (SPSS) was used to analyze the data. Results The study found that 50% of the participants said that HIV patient who had mental illness were not responsible for their illness, HIV patients who have mental illness are more dangerous to the general public, 70% said that it is not true, (73%) said that HIV and mental illness are related, (96.7%) said they would recommend pharmacotherapy, counselors (50%) found that clients with emotional problems was their major challenge about the patients, 12(40%) said clients with strange behavior and (54%) said they would confront the problem. Conclusion Although HIV counselors portrayed a sense of self-efficacy to manage mental health problems among their HIV positive clients, their interventions were limited by their lack of expertise to deal with specific mental health problems. Recommendations Training needs assessment for HIV counselors, enhancing integration of mental health care in HIV service provision, improving awareness needs to be built among HIV counselors about the mental health problems that affect people living with HIV/AIDS, HIV service provision policies to be revised to emphasize mental health aspects.